ANALISIS PRAKTIK ETIKA BISNIS SYARIAH (STUDI KASUS PASAR LEUWILIANG) - Ira Puspitasari (AMWALUNA (Jurnal Ekonomi dan Keuangan Syariah), 2019)
In Islam, ethics is a character as a form of self-development towards human relations with Allah SWT and human relations with fellow beings. This study aims to determine sharia business ethics among Muslim traders in the Leuwiliang market. Data collection methods are carried out using qualitative methods. This research informant numbered 25 people. This data was obtained from interviews with traders at the Leuwiliang market. The results of the study found that not all traders in Leuwiliang Market were aware of sharia business ethics, but from the answers they gave regarding maintaining product halal and how to maintain customer trust it could be said that they had at least implemented business ethics in sharia.